Roadmap for the emerging field of cancer neuroscience - Monje, Michelle; Borniger, Jeremy C.; D’Silva, Nisha J.; Deneen, Benjamin; Dirks, Peter B.; Fattahi, Faranak; Frenette, Paul S.; Garzia, Livia; Gutmann, David H.; Hanahan, Douglas; Hervey-Jumper, Shawn L.; Hondermarck, Hubert; et al. (Cell, 2020)
Mounting evidence indicates that the nervous system plays a central role in cancer pathogenesis. In turn, cancers and cancer therapies can alter nervous system form and function. This Commentary seeks to describe the burgeoning field of “cancer neuroscience” and encourage multidisciplinary collaboration for the study of cancer-nervous system interactions.
Gesehen am 15.04.2021